(untitled) (Advancements in Homeopathic Research, 2022)
A total of 100 well diagnosed cases of Vitiligo were registered for treatment from October 2016 to October 2018. Clinical diagnosis followed by constitutional treatment with homoeopathic medicines showed amazing results in majority of cases. Out of 100 cases 25 cases showed complete repigmentation of all the white patches while 29 cases showed much improvement in few patches and rest 29 cases did not show any response to the treatment. 17 cases worsened after treatment in which increment in size and number of white patches was observed. Duration of treatment varied from case to case depending on the size and number of the white patches and response of the patient. In depth case taking was done in each and every case on holistic principle giving more emphasis on causation and mental symptoms. The outcome of this study is very encouraging which gives new dimensions and confidence to young Homoeopaths in the treatment of Vitiligo by Hahnema anian principles of minimum dose and minimum repetition.